Duck takes off - Gretz, Susanna (New York : Four Winds Press, 1991)
Duck, Rabbit, and Frog have trouble playing school when each possesses such different skills from the other.
Keywords: Animals -- Fiction; Friendship -- Fiction; Play -- Fiction